2021
DOI: 10.1039/d1cc01298c
|View full text |Cite
|
Sign up to set email alerts
|

Bicyclic (alkyl)(amino)carbene stabilized zinc(0) complex with singlet biradicaloid ground state

Abstract: A storable bicyclic (alkyl)(amino)carbene (BICAAC) stabilized two coordinate zinc(0) complex [(BICAAC)2Zn] (2) was synthesized. DFT calculations reveal that BICAAC plays decisive role for imparting the stability of 2. This complex...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…[36] The zincÀ halide bond lengths progressively increase in a row Cl > Br > I (Figure 1), whereas the ZnÀ C carbene bonds of 1-3 show only minor variations and are very similar to those found for the NHC-and BIcAAC-based dimers mentioned above (~2.0 Å). [34][35][36] Dimers 1-3 are not soluble in aliphatic or aromatic hydrocarbons, or chlorinated solvents; however, they could be redissolved in acetonitrile for further characterization by multinuclear NMR spectroscopy (see Experimental Section). Coordination of the Me cAAC ligand to the Zn II ion leads to a significant upfield shift of the C carbene resonance in the 13 C{ 1 H} NMR spectra in CD 3 CN to ~250 ppm for 1-3 compared to 304.2 ppm of free Me cAAC.…”
Section: Synthesis and Characterizationsupporting
confidence: 70%
See 1 more Smart Citation
“…[36] The zincÀ halide bond lengths progressively increase in a row Cl > Br > I (Figure 1), whereas the ZnÀ C carbene bonds of 1-3 show only minor variations and are very similar to those found for the NHC-and BIcAAC-based dimers mentioned above (~2.0 Å). [34][35][36] Dimers 1-3 are not soluble in aliphatic or aromatic hydrocarbons, or chlorinated solvents; however, they could be redissolved in acetonitrile for further characterization by multinuclear NMR spectroscopy (see Experimental Section). Coordination of the Me cAAC ligand to the Zn II ion leads to a significant upfield shift of the C carbene resonance in the 13 C{ 1 H} NMR spectra in CD 3 CN to ~250 ppm for 1-3 compared to 304.2 ppm of free Me cAAC.…”
Section: Synthesis and Characterizationsupporting
confidence: 70%
“…The structures of 1 – 3 in the single‐crystalline solid state can be viewed as two pseudo‐tetrahedral {( Me cAAC)Zn(μ‐X) 2 X} units sharing one edge consisting of two bridging halides, with overall approximate D 2 symmetry. Only a few analogous Zn II carbene complexes have been reported in the literature to compare the structural parameters, which are [(IPr)BrZn(μ‐Br) 2 ZnBr(IPr)] [34] (IPr=1,3‐dimesityl‐imidazol‐4,5‐dihydro‐2‐ylidene), [(IPr’)ClZn(μ‐Cl) 2 ZnCl(IPr’)] [35] (IPr’=1‐mesityl‐3‐(methoxyethanyl)‐imidazol‐4,5‐dihydro‐2‐ylidene) and [(BIcAAC)ClZn(μ‐Cl) 2 ZnCl(BIcAAC)] (BIcAAC=bicyclic (alkyl)(amino)carbene) [36] . The zinc−halide bond lengths progressively increase in a row Cl > Br > I (Figure 1), whereas the Zn−C carbene bonds of 1 – 3 show only minor variations and are very similar to those found for the NHC‐ and BIcAAC‐based dimers mentioned above (∼2.0 Å) [34–36] …”
Section: Resultsmentioning
confidence: 99%
“…42f In 2021, Mandal et al reported a two-coordinate Zn (0) complex, (BICAAC) 2 Zn (Scheme 15). 43 Similar to (CAAC) 2 Zn, (BICAAC) 2 Zn is a singlet biradicaloid complex and was investigated by DFT calculations. (BICAAC) 2 Zn can be stored indefinitely at room temperature in an inert atmosphere and is stable for 24 h in degassed water (10 equiv.…”
Section: Bicaacmentioning
confidence: 99%
“…7 Recently, our group reported a BICAAC-stabilized Zn(0) complex and its reactivity with CO 2 and Ph 3 CCl. 8 In addition, BICAACs have attracted interest as a ligand in metal catalysed cross coupling reactions and terminal alkyne protoboration. 9,10…”
mentioning
confidence: 99%